1998
DOI: 10.1038/sj.bdj.4809563
|View full text |Cite
|
Sign up to set email alerts
|

Audit activity and uptake of postgraduate dental education among general dental practitioners in Yorkshire

Abstract: The aim of this study was to assess the involvement of general dental practitioners in Yorkshire in clinical audit activity and in postgraduate dental education and to compare the results with those of a previous survey undertaken in 1989. There is a need to find ways of encouraging all general dental practitioners to become actively involved in continuing professional development and in improving the quality of general dental practice through the use of clinical audit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
1
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 0 publications
0
27
1
1
Order By: Relevance
“…To address the problems a range of videos, 2 manuals 3,4 and computer-aided learning programmes 5 have been developed at public expense 6 and distributed free of charge to dentists working in Primary Dental Care within the NHS. A more recent study 7 indicates that in one English region during the 1990s there has been an improvement in Participating dentists' assessment of the pilot regional online videoconferencing in dentistry (PROVIDENT) project K A Eaton, 1 C A Francis, 2 E W Odell, 3 P A Reynolds 4 and R D Mason 5 the numbers of dentists attending CPD courses. A further stimulus to CPD has arisen from the General Dental Council's (GDC's) recently launched voluntary scheme 8 which requires a UK registered dentist to take part in CPD throughout his or her practising career.…”
Section: Education Videoconferencingmentioning
confidence: 99%
“…To address the problems a range of videos, 2 manuals 3,4 and computer-aided learning programmes 5 have been developed at public expense 6 and distributed free of charge to dentists working in Primary Dental Care within the NHS. A more recent study 7 indicates that in one English region during the 1990s there has been an improvement in Participating dentists' assessment of the pilot regional online videoconferencing in dentistry (PROVIDENT) project K A Eaton, 1 C A Francis, 2 E W Odell, 3 P A Reynolds 4 and R D Mason 5 the numbers of dentists attending CPD courses. A further stimulus to CPD has arisen from the General Dental Council's (GDC's) recently launched voluntary scheme 8 which requires a UK registered dentist to take part in CPD throughout his or her practising career.…”
Section: Education Videoconferencingmentioning
confidence: 99%
“…It has been shown however, that postgraduate course attendance, either Section 63 or private, had been a major catalyst in causing GDPs in the Yorkshire Region to modify the way they practised dentistry, 6 although the level of participation has decreased in comparison to a previous study carried out in 1989. 8 Demand for longer and more intensive courses is evidenced by the success of the Bristol University Open Learning for Dentists (BUOLD) initiative provided by Bristol University, which offers both a distance learning component and summative assessment leading to a registerable qualification.…”
mentioning
confidence: 42%
“…Although this question included all postgraduate education courses and not just Section 63, this appears to compare favourably with a study carried out among GDPs in Yorkshire. 6 Earlier studies in 1991 and 1993 also indicated a low uptake of Section 63 courses by GDPs both from a self-reporting questionnaire, 11 and from Family Health Service Authority (FHSA) data. 12 The results from this present study suggest an increased commitment to postgraduate education, however, it was impossible to validate the GDPs sessional attendance at postgraduate courses due to the anonymous nature of the survey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence of considerable, if varied, take-up of these opportunities. 4,5,6,7 A recent study, 8 found enthusiasm for postgraduate courses: eight-nine per cent of the study group had attended two or more sessions within the last twelve months. However, they note that in order to meet the GDC's recertification proposals, the majority of the group would need to further increase their level of participation, raising 'formidable challenges for providers of postgraduate education in meeting potential future demand' .…”
mentioning
confidence: 99%